Thermophotovoltaics: Large‐Area Ultrabroadband Absorber for Solar Thermophotovoltaics Based on 3D Titanium Nitride Nanopillars (Advanced Optical Materials 22/2017). Issue 22 (16th November 2017) - Chirumamilla, Manohar; Chirumamilla, Anisha; Yang, Yuanqing; Roberts, Alexander S.; Kristensen, Peter Kjær; Chaudhuri, Krishnakali; Boltasseva, Alexandra; Sutherland, Duncan S.; Bozhevolnyi, Sergey I.; Pedersen, Kjeld
Abstract : Manohar Chirumamilla and co‐workers introduce a novel thermally stable ultra‐broadband absorber for solar thermophotovoltaics based on refractory 3D titanium nitride nanopillars in article number1700552 . Scalable large‐area costeffective fabrication methods combined with omnidirectionality, polarization insensitivity, and high thermal/chemical/structural/spectral stability, make the 3D titanium nitride nanopillars very interesting candidates for high‐temperature photonic and plasmonic applications.